Jefferson, Lincoln, and the Unfinished Work of the Nation - Hatzenbuehler, Ronald L. (Book collections on Project MUSE., 2016)
Although the nation changed substantially between the presidential terms of Thomas Jefferson and Abraham Lincoln, these two leaders shared common interests and held remarkably similar opinions on many important issues. In Jefferson, Lincoln, and the Unfinished Work of the Nation, Ronald L. Hatzenbuehler describes the views of two of our nation's greatest presidents and explains how these views provide valuable insight into modern debates. In this groundbreaking new study-the first extended examination of the ideas of Lincoln and Jefferson-Hatzenbuehler provides readers with a succinct guide to.